Disseminated Gonococcal Infection in Mice - Corbeil, Lynette B. (1979)
Gonococci do not readily cause disseminated infection in mice. To simulate some of the conditions leading to disseminated gonococcal infection in women, we suspended gonococci in mucin plus hemoglobin and studied the development of gonococcal bacteremia. The mucin-hemoglobin mixture was used because the menstruum appears to be involved in dissemination of gonococci from the genital tract during menstruation. Mice did not die after massive inocula of 10(9) gonococci given intraperitoneally in broth, but when gonococci were suspended in mucin (15%) alone, the 50% lethal dose was 10(8.4) and in 15% mucin plus 4% hemoglobin (M/H), the 50% lethal dose fell to 10(6.6). Sublethal doses produced local peritonitis and transient bacteremia. With larger inocula the local peritoneal infection progressed to fatal septicemia. Studies of the mechanism by which M/H lowered the 50% lethal dose showed that systemic clearance mechanisms were compromised, but not enough to account for the total decrease in the 50% lethal dose. If gonococci were given intravenously after intraperitoneal inoculation of M/H, sequestration of gonococci in the peritoneal cavity occurred, suggesting an effect on local peritoneal defenses. The effect on neutrophils appeared most significant, since numbers of neutrophils in the peritoneal fluid were decreased in the presence of M/H and neutrophils were destroyed by M/H in vitro. The serum bactericidal system was not affected. We conclude that M/H promotes gonococcal bacteremia by interference with phagocytosis and intracellular killing of gonococci. The model simulates the disseminated gonococcal infection cases in women which follow pelvic inflammatory disease in its progression from local peritonitis to transient or lethal bacteremia and in factors (mucin and hemoglobin) which enhance infection.